Parent’s Roles in Promoting Resilience of Preschoolers During the Covid-19 - Saksuphan, Nidanuch; Khayankij, Sasiluk (An Online Journal of Education, 2022)
This survey research aimed to study parents’ roles in promoting public school preschoolers’ resilience during COVID-19 pandemic in two aspects, reassurance and extended experience. The sample consisted of 126 preschool parents, and the research instrument used was a questionnaire. The data were analyzed using percentage, means, and standard deviation. The research found that parents’ roles in promoting preschoolers’ resilience during the COVID-19 pandemic was performed at a high level in both aspects (M = 4.07). Thus, the parents communicated with their children, provided appropriate information, gave warmth and love, took care of daily routines, and organized activities that promoted knowledge for their children. Both aspects were found to be at a high level; extended experience had the highest mean score (M = 4.07), followed by reassurance (M = 4.06). The results show that the parents paid attention to the children’s daily routines, helped them learning through activities rather than direct communication, and gave the children warmth and love.